2022
DOI: 10.1155/2022/5135817
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Fitness Status and Blood Biomarkers in Professional Soccer Players

Abstract: Background. Physical conditions are recognized to be optimal after the pre-season (PS) phase in professional sports. Given that blood measures may also reveal variations, which in turn, may present associations with fitness changes. Objective. The aim of this study is to test the changes of blood markers and physical fitness outcomes at the beginning and following the PS phase. Additionally, we aimed also to analyze the associations of training adaptations between blood markers and the physical fitness measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…Lastly, our study highlights the importance of home-based training during the COVID-19 lockdown, off-season, and competitive season in order to minimize the decremental effect of long-term detraining on aerobic capacity, to target improvement in VO2max performance, and reduce injury susceptibility. Considering the relationship between superior aerobic performance and some hematological parameters (hematocrit concentration, erythrocyte, hemoglobin concentration, mean corpuscular hemoglobin concentration) [32][33][34], it is possibly important that the coaches evaluate their players in terms of hematological parameters at certain time intervals in order to plan and facilitate the return of the players to training, especially after a long-term detraining period.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, our study highlights the importance of home-based training during the COVID-19 lockdown, off-season, and competitive season in order to minimize the decremental effect of long-term detraining on aerobic capacity, to target improvement in VO2max performance, and reduce injury susceptibility. Considering the relationship between superior aerobic performance and some hematological parameters (hematocrit concentration, erythrocyte, hemoglobin concentration, mean corpuscular hemoglobin concentration) [32][33][34], it is possibly important that the coaches evaluate their players in terms of hematological parameters at certain time intervals in order to plan and facilitate the return of the players to training, especially after a long-term detraining period.…”
Section: Discussionmentioning
confidence: 99%
“…21 Blood is considered as a tissue whose molecular profile reflects all important changes occurring in the whole organism under given conditions. 22 Moreover, blood can be a useful source of biomarkers reflecting exercise-induced modifications 22,23 without the need to perform a tissue or organ biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…However, a decreasing trend of CRP can be noticed. Studies investigating biochemical markers after overnight fasting and rest in soccer players performing preseason low aerobic physical activity showed an increase in CRP values after the preseason training [ 28 , 29 ]. The study showed that training leads to greater inflammation at the beginning of the season than at the end, while some studies that followed athletes (soccer and basketball players) over a longer period of time showed an increase in CRP values [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%